Soft start-up strategy of pulse-density-modulated series-resonant converter for induction heating application - Pavlo Herasymenko; Volodymyr Pavlovskyi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper presents a soft start-up strategy of pulse-density-modulated series-resonant converter for induction heating application. The pulse-density modulation (PDM) technique is widely used in converters based on voltage-source series-resonant inverters (SRIs) to control the output current or power. However, during a start-up process, PDM has some disadvantages both in inrush current limiting and providing a zero-voltage switching operation of SRI transistors. In the paper, different PDM techniques are considered and basic moments of PDM using within the start-up process are analyzed. A new soft start-up strategy of PDM converter for induction heating application is proposed. The main features of the proposed strategy include an interleaved or a stepped PDM control, an initial combination of PDM at the beginning of the start-up process, and an operating algorithm during the start-up process. The proposed strategy was verified by a 2.5 kW experimental setup of the pulse-density-modulated interleaved converter with an operating frequency from 50 kHz up to 100 kHz. Experimental results confirm the effectiveness of the proposed start-up strategy and show that the maximum current amplitude within start-up processes exceeds the maximum steady-state current amplitude by no more than 30%.